WAYS TO INCREASE OCCUPATIONAL SAFETY ON RAILWAY TRANSPORT OF UKRAINE: Array - Vorozhbiian, M.; Ivashchenko, M.; Skrypnyk, O. (Municipal economy of cities. Series: «Economy science», 2022)
One of the main indicators of the state of labor protection at any enterprise is the level of occupational injuries and occupational diseases. Injuries to workers at work in Ukraine are a very serious problem. The article analyzes the statistics of Ukraine and the European Union on general and fatal injuries in recent decades, found that occupational injuries in Ukraine are much higher. OSMS in Ukraine is ineffective in modern conditions, as it is not based on risk-oriented approaches aimed at preventing the realization of hazards by studying the risks and conditions of their implementation. In order to objectively assess the state of labor protection in railway transport, the general state of accidents and occupational diseases in Ukraine is considered. Railway transport is one of the main components of Ukraine’s economy, and the state of labor protection at its enterprises is important for both employees and railway users. It is very important in the period of reforming the industry and the transition to high-speed traffic to analyze the causes of accidents, identify risks that can lead to injuries and manage them, which is the purpose of this work. Research in this area was conducted through an analytical review of legislative and regulatory documents, as well as an analysis of the state of labor protection in the industry in recent years. Statistical analysis of occupational injuries in Ukraine was also used. It is established that injuries in the period 2000-2021 on railway transport decreased by 2 times, and the number of employees - by 1.8 times. To reduce the level of occupational injuries at railway enterprises, the main measures are proposed, which should primarily be based on a risk-oriented approach. The general policy for the prevention of industrial risks should cover the technical, organizational, social component and take into account the impact of factors related to the working environment, including proper training of workers on occupational safety. It is necessary to systematically conduct comprehensive, control and targeted inspections of the state of labor protection at railway transport enterprises, to exclude a formal approach to inspections.